Diaphyseal Femur Fracture in Paediatric Age group: Outcome with fixation by Elastic Nailing System - Panthi, Sagar; Shrestha, Rishiswor; Pradhan, Jigyasu; Neupane, Bikash; Bhusal, Ishory; Karki, Angelica (Europasian Journal of Medical Sciences, 2021)
Background: Diaphyseal femur fracture in paediatric age group account for 1.6% of all paediatric fractures. Fracture fixation by elastic nail provides three point fixation. This study aims to assess the outcome of diaphyseal femur fracture in paediatric age group from 5 to 15 years treated with titanium elastic nailing system. Methods: Thirty six patients with diaphyseal femur fracture were treated with titanium elastic nailing system from November 2018 to August 2020 was analyzed prospectively. All the patients were followed up for six months for the study. Final outcome was evaluated at six months. Results: The mean time of fracture union was 9.12 weeks. Two patients had limb lengthening of 6 mm and 8 mm respectively. One patient had 1 cm of shortening and 8 degree of varus angulation and 9 patients had bursitis over nail insertion site. According to Flynn grading 26 cases have excellent results (72.22%) and 10 cases have satisfactory results (27.78%). Conclusion: Diaphyseal femur fracture can be treated with elastic nailing system with early mobilization and good functional outcomes.